A Study of Molecular Mimicry and Immunological Cross-reactivity between Hepatitis B Surface Antigen and Myelin Mimics - Dimitrios-Petrou Bogdanos; Heather Smith; Yun Ma; Harold Baum; Giorgina Mieli-Vergani; Diego Vergani (Clinical and Developmental Immunology)
On the basis of the reported association between hepatitis B vaccination (HBvacc) and autoimmune demyelinating complications such as multiple sclerosis (MS), we have looked for aminoacid similarities between the small hepatitis B virus surface antigen (SHBsAg), and the MS-autoantigens myelin basic protein (MBP) and myelin oligodendrocyte glycoprotein (MOG) that could serve as targets of immunological cross-reactivity. Twenty-mer peptides spanning 4 SHBsAg/MOG and 1 SHBsAg/MBP mimicking pairs, were constructed and tested by ELISA as targets of cross-reactive responses. A total of 147 samples from 58 adults were collected before HBvacc (58/58), and post-HBvacc (48/58 before the second and 41/58 before the third boost). Eighty-seven sera from anti-SHBsAg antibody negative patients with various diseases were tested as pathological controls. Reactivity to at least one of the SHBsAg peptides was found in 8 (14%) pre-HBvacc subjects; amongst the remaining 50, reactivity to at least one of the SHBsAg peptides appeared in 47 (94%) post-HBvacc. Reactivity to at least one of the MOG mimics was present in 4 (8%) pre-HBvacc and in 30 (60%) post-HBvacc (p < 0.001). Overall 30/50 (60%) vaccinees had SHBsAg/MOG double reactivity on at least one occasion compared to none before-vaccination and in 2 (2%) of the pathological controls (p < 0.001 for both). SHBsAg/MOG double reactivity was cross-reactive as confirmed by inhibition studies. At 6 months post-vaccination, 3 of the 4 anti-MOG reactive cases before vaccination and 7 of the 24 (29%) of the anti-MOG reactive cases at 3 months post-vaccination had lost their reactivity to MOG5-24. There was no reactivity to the SHBsAg/MBP mimics. None of the vaccinees reported symptoms of demyelinating disorders. In view of the observed SHBsAg/MOG cross-reactivity, the vaccine's possible role as an immunomodulator of viral/self cross-reactivity must be further investigated.